Low-beta strategies - Olaf Korn; Laura-Chloé Kuntz (University of Cologne, Centre for Financial Research (CFR), 2017)
This paper analyzes trading strategies designed to exploit the low-beta anomaly. Although the notion of buying low-beta stocks and selling high-beta stocks is natural, a choice is necessary with respect to the relative weighting of high-beta stocks and low-beta stocks in the portfolio. Our empirical results for US stocks show that this choice is very important for the risk-return characteristics of the resulting portfolios and their sensitivities to common risk factors. The weighting of stocks within the low-beta and high-beta portfolios and the chosen investment universe are essential design elements of low-beta strategies too. If smaller firms are excluded, risk-adjusted returns of low-beta strategies can even become insignificant.
Keywords: G11; G12; G14; 330; low-beta anomaly; trading strategies; factor risk premiums; smart beta